Development of information system components for management of bus transportation processes - Pekaruk, I. O. (ХНУРЕ, 2024)
This article conducts an analysis of the subject area concerning the development of information system components for the management of bus transportation processes. It aims to define the primary objectives of the work, including identifying key business requirements crucial for efficient bus transportation management. Furthermore, it entails selecting appropriate technologies tailored to meet the demands of the project. Overall, this work would be will be beneficial to stakeholders involved in the development and management of bus transportation systems.
Keywords: information system; management